Geometrical model establishment and preoperative evaluation on A-T flap design: Finite element method-based computer-aided simulation on surgical operation processes - Zhao, Yan; Yang, Zonglin; Chen, Lifen; Peng, Yuhui (Frontiers in Surgery, 2022)
Objective: A-T flap has been extensively applied to repair dermal soft tissue defects. The flap design completely depends on the experience of doctors. Herein, we explored the approach of analyzing the reasonability of A-T flap design and performed a simulation of operation processes by computer-aided technology. Afterward, the finite element analysis software (MSC.Marc/Mentat) was used to establish the simulation model, based on which the computer simulation of flap suturing and release state in A-T flap surgery was performed. Methods: A geometrical model of the A-T flap was established, and the length-width ratio of the flap, maximum suture distance, and suture area that could influence the postoperative suture effects of the flap were analyzed. The reasonable surgical planning for A-T flap design based on the crossing constraint relationship was achieved. The simulation model was established by the finite element analysis software (MSC.Marc/Mentat), based on which computer simulation of flap suture and release state of A-T flap in surgery processes were performed. The flap's stress and deformation distribution results confirmed the applicability of the A-T flap design method proposed in the present study. Results: When the apex angle of the A-T flap was 60 degrees, the suture area was the smallest, and the flap design had the highest practicability. Conclusion: Computer-assisted preoperative assessment, which has high clinical value, could provide a theoretical basis for A-T flap design in clinical practice.